Film theory and criticism - Leo Braudy (Oxford University Press, 2004)
Since publication of the first edition in 1974, Film Theory and Criticism has been the most widely used and cited anthology of critical writings about film. Extensively revised and updated, this sixth edition highlights both classic texts and cutting edge essays from more than a century of thought and writing about the movies. Editors Leo Braudy and Marshall Cohen have reformulated the book's sections and their introductions in order to lead students into a rich understanding of what the movies have accomplished, both as individual works and as contributions to what has been called "the art form of the twentieth [and now twenty-first] century"